Close collaboration between local and specialist multidisciplinary teams allows 'fast‐tracking' of patients with colorectal liver metastases. (24th October 2013) - Vasudevan, S. P.; Cresswell, A. B.; Wright, J. M.; Rees, M.; Stiff, D.; Wordley, A.; Motson, R. W.
Abstract: Aim: The ongoing evolution of treatment strategies for colorectal liver metastases necessarily requires all patients to be reviewed at some point by the specialist hepatobiliary unit. This process can be streamlined through close collaboration with the local colorectal multidisciplinary team (MDT). The study was performed to see if a local colorectal MDT was able to make a correct decision regarding potential operability of liver metastases, by comparing its decision with that of two hepatobiliary surgeons in our referral centre. Method: CT scans of 38 patients found to have liver metastases from colorectal cancer were anonymized and sent to two hepatobiliary surgeons in our cancer network. They classified them into three categories: R, resectable; C, chemotherapy to downsize then consider resection; U, unresectable. The results were then compared with the opinion of our colorectal MDT, made before the referral to the hepatobiliary surgeons. Results: The two independent hepatobiliary surgeons agreed with each other on 35/38 (92%) of CT scans. Our colorectal MDT agreed with the hepatobiliary surgeons in 36/38 (95%) of cases. Only 9 (32%) of the 28 patients deemed suitable on the CT scan by the hepatobiliary surgeons actually had a liver resection. Conclusion: The results show that a local colorectal MDT is able to make an accurate assessment of the operability of liver metastases. Patients deemed to be inoperable by the colorectal MDT could be 'fast‐tracked' to the hepatobiliary MDT with review of imaging only, saving time and resources by avoiding referral of patients who are not suitable for liver resection.